2023
DOI: 10.1186/s12864-023-09491-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification of cuproptosis-related molecular subtypes as a biomarker for differentiating active from latent tuberculosis in children

Liang Chen,
Jie Hua,
Xiaopu He

Abstract: Background Cell death plays a crucial role in the progression of active tuberculosis (ATB) from latent infection (LTBI). Cuproptosis, a novel programmed cell death, has been reported to be associated with the pathology of various diseases. We aimed to identify cuproptosis-related molecular subtypes as biomarkers for distinguishing ATB from LTBI in pediatric patients. Method The expression profiles of cuproptosis regulators and immune characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The six mRNA biomarkers indicated extraordinary performance in distinguishing active tuberculosis patients from healthy controls, with AUC values ranging from 0.912 to 0.995. Furthermore, we compared the diagnostic efficiency of these six mRNA biomarkers with other tuberculosis biomarkers; , in comparison to existing tuberculosis biomarkers, our six mRNA biomarkers demonstrated superior or equivalent diagnostic accuracy in differentiating ATB patients from healthy controls (Figure A and Figure S12) and ATB patients from LTBI (Figure A and Figure S13). We next explored the connection between the TBMMRP and relevant clinical features; in contrast to the controls or the LTBI group, ATB patients had considerably higher estimated risk probabilities based on the TBMMRP model, but there were no notable changes between the two groups in terms of BCG-vaccinated or gender variations across various cohorts (Figures S14 and S15).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The six mRNA biomarkers indicated extraordinary performance in distinguishing active tuberculosis patients from healthy controls, with AUC values ranging from 0.912 to 0.995. Furthermore, we compared the diagnostic efficiency of these six mRNA biomarkers with other tuberculosis biomarkers; , in comparison to existing tuberculosis biomarkers, our six mRNA biomarkers demonstrated superior or equivalent diagnostic accuracy in differentiating ATB patients from healthy controls (Figure A and Figure S12) and ATB patients from LTBI (Figure A and Figure S13). We next explored the connection between the TBMMRP and relevant clinical features; in contrast to the controls or the LTBI group, ATB patients had considerably higher estimated risk probabilities based on the TBMMRP model, but there were no notable changes between the two groups in terms of BCG-vaccinated or gender variations across various cohorts (Figures S14 and S15).…”
Section: Resultsmentioning
confidence: 99%
“…To create a clinically adaptable mRNA-based active tuberculosis model for estimating the risk probability of developing active 0.907−0.947, sensitivity: 81.25%, specificity: 87.75%) (Figure 5A), and a BIIR cohort (103 ATB and 69 LTBI) with an AUC of 1.000 (95% CI: 1.000−1.000, sensitivity: 100.00%, specificity: 100.00%) (Figure 5B). , 32 Xu et al, 19 Qiu et al, 21 Yi et al, 31 Chen et al, 22 Wu et al, 33 and Geng et al We assessed the diagnostic performance in four fully blinded external cohorts with various platforms. The discriminatory capacity of 13 ATB from the first external cohort and 17 LTBI in England from the BIIR-1 cohort was examined; the results showed the favorable performance of differentiating ATB from LTBI with an AUC of 0.991 (95% CI: 0.937−0.995, sensitivity: 92.30%, specificity: 94.12%) (Figure 5C).…”
Section: Detection Of Differentially Expressed Genes Of Dadcseqmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on previous research on cuproptosis, we identified 19 CRGs ( 11 , 12 ) After obtaining gene expression data, in R software 4.3.0, we used the “limma” package to correct the data. We identified differentially expressed CRGs (DE-CRGs) (P<0.05) between the major burn group and control group.…”
Section: Methodsmentioning
confidence: 99%